THE OPTIMIZATION OF THE MODEL OF THE STRENGTHENED LAYER BY THE SURFACE STRENGTHENING - А.А. LAVRENTYEV; I.Е. ROGOV; S.D. ANISIMOV; V.S. KOVALEVA (Advanced Engineering Research, 2009)
The parameters of the imitative model of multilayer conductive ferromagnetic media to achieve the optimal precision of modeling are determined. The experimental investigation of the distribution of physicomechanical and electromagnetic properties along the thickness of the sample have been carried out. The standard epures of these properties were determined. The parameters of the imitative model of the multilayer conductive ferromagnetic media to achieve the optimal precision of modeling are determined.